Assistance in the preparation of Classroom Action Research articles and publications in reputable national journals - Sri Asnawati; Irmawati Liliana Kusuma Dewi; Tri Nopriana; Siska Firmasari (University of Merdeka Malang, 2021)
Writing scientific papers is an important activity to improve teachers' quality, competence, and professionalism. Its implementation is marked by, among others, self-improvement through scientific research in the form of Classroom Action Research. During teaching and learning activities, teachers can research by developing various instruments and learning strategies. However, teachers rarely put their research results in writing in research reports and scientific articles. This community service activity aims to assist teachers in compiling Classroom Action Research reports and articles and explaining tricks to publish Classroom Action Research articles in reputable national journals. The implementation of the activities uses the methods of training, discussion, and direct mentoring so that the teacher can feel the process. This service activity received a good response, with the teacher's enthusiasm during the exercise, active discussions, and scientific reports and articles compilation. In the final discussion of this community service activity, teachers are very interested in publishing the results of their research, and it's just that teachers lack information about reputable journals. Through this activity, the ability of teachers to research and publish their research results can become practical innovations in the world of education, especially classroom learning.